"Innovation policy is a team sport": Insights from non-governmental intermediaries in Canadian innovation ecosystem - Merli Tamtik (Triple Helix, 2018)
Policy-makers and practitioners alike have increasingly embraced the innovation ecosystem approach to support the flow of knowledge within the Triple Helix framework. This approach focuses on the collaborative and interdependent nature of innovation, which is based on social aspects of knowledge transfer supporting relationships, partnerships, and connections. The important role of intermediary stakeholders that help to facilitate such partnerships is under-researched. This paper examines the work of three intermediary stakeholders in the Canadian innovation ecosystem-the Canadian Science Policy Centre, the MaRS Discovery District, and university Vice Presidents Research. By interviewing 40 experts from the federal and provincial governments, non-governmental organizations, industry, and the higher education sector in Ontario, this study examines how innovation ecosystems are created and what factors influence the success of bringing diverse stakeholders together. The findings suggest that strong political vision and leadership, an inclusive approach to recognizing the needs of diverse stakeholders, and clarity on ways to measure and fund innovation serve as important factors in the Canadian innovation ecosystem.
Keywords: 330; Innovation ecosystem; Intermediary stakeholders; Non-governmental agents; Canada